Ants (Hymenoptera: Formicidae) associated with pig carcasses in Malaysia - Chin, H.C.; Marwi, M.A.; Hashim, R.; Abdullah, N.A.; Dhang, C.C.; Jeffery, J.; Kurahashi, H.; Omar, B. (2009)
An observational study was conducted in an oil palm plantation in Tanjung Sepat, Selangor, Malaysia on August until September 2007 to note the decomposition process of pigs and their related faunal succession. We collected six species of ants (Formicidae) from 3 subfamilies: Formicinae (Oecophylla smaragdina and Anoplolepis gracilipes), Myrmicinae (Tetramorium sp. and Pheidologeton sp.) and Ponerinae (Odontoponera sp. and Diacamma sp.) that were associated with pig carcasses placed on the ground. Oecophylla smaragdina, Pheidologeton sp. and Tetramorium sp. were found on a partially burnt pig carcass whereas the other species were recovered from unburned pig carcass. These ants predated on fly eggs, larvae, pupae and adults. Ants could be found at all stages of decomposition starting from fresh until dry stage. Predatory ants can reduce fly population and thus may affect the rate of carcass decomposition but this was not seen in our study. Even though O. smaragdina was seen at all stages of decomposition of the burnt pig, this did not alter much the decomposition process by fly larvae.